De l'âge du Bronze à l'âge du Fer en France et en Europe occidentale (Xe-VIIe siècle av. J.-C.) La moyenne vallée du Rhône aux âges du Fer - Roulière-Lambert, Marie-Jeanne (Suppléments à la Revue archéologique de l'Est, 2009)
So dynamic was archaeology in Lyon and its surrounding region (Macon, the Loire Country and the Alps), that focus was kept on regional topics and that the question of «territory» was kept as the main line of research. The question has been tackled from many angles: written sources, enlightening summaries and synthetized works, presentation of quite remarkable sites, whether settlement sites or burial sites. The whole point was to shed light on the transitional phase between the Bronze Age and the Iron Age. What are the signs of a change, how to explain them, how to pinpoint them? Most scientists have led their research on a fairly large time span, always in the perspective of an endogenous evolution. The metal criterion do not come up as the most relevant factor anymore. Differenciation in pottery groups and disruption in the cultural cohesion prevail between the XIIthand the VIIth centuries. New practices arise in settlement patterns as well as funeral rites: the situation in Europe here under study, is richly contrasted and documented with case studies coming from a zone spreading from Spain to Italy, from Great Britain to Bohemia. The records of the 30th «A.F.E.A.F., Association Française pour l'Étude de l'Âge du Fer» 'symposium - Saint-Romain en Gal, 2006 - gather in one single volume the 16 papers on regional issues, as well as 28 papers on more specific issues, organized in collaboration with the Association pour la Promotion des Recherches sur l'âge du Bronze (A.P.R.A.B.).